Pengaruh Inovasi Pemasaran Terhadap Keputusan Transaksi Pengguna OVO - Sari, Siti Nur Kurnia; Hawignyo, Hawignyo (Peneliti.net, 2025)
This study aims to determine the effect of marketing innovation on OVO user transaction decisions. The research method used in this study uses a quantitative approach with the population used, namely OVO application users in Karawang Regency. The sample in this study was 150. In determining the sample, the researcher used a random sampling technique. The data analysis used in this study is simple regression analysis. The results of this study are Based on the results of the research analysis, it is known that marketing innovation has a significant effect on transaction decisions. The existence of this significant influence indicates that marketing innovation increases the number of OVO Fintech user transaction decisions, thus creating positive things for progress and welfare so as to increase income at the OVO Fintech company. The results of the simple linear regression test, it is known that the variables of marketing innovation and transaction decisions together or simultaneously and significantly affect the increase in transaction users at OVO Fintech. The results of the research analysis show that marketing innovation and transaction decisions simultaneously have a significant effect on OVO Fintech revenue. The results of this analysis indicate that it is in accordance with the research hypothesis, the income of the OVO Fintech company by the two variables studied, namely marketing innovation and transaction decisions. The regression coefficient of the marketing innovation variable is positive.